A COMPREHENSIVE ANALYSIS OF RATIONAL AND IRRATIONAL FIXED DOSE COMBINATIONS OF ANTIBACTERIAL DRUGS AVAILABLE IN THE INDIAN MARKET - Dr.Pooja Solanki Mishra; Dr.Meghna Shinde; Dr.Paroma Sinha (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
INTRODUCTION: Fixed Dose Combinations (FDCs) are products containing two or more active ingredients used for a particular indication, in a fixed ratio of doses. Today, there is a growing concern about the burgeoning list of irrational Fixed Dose Combinations (FDCs) that have flooded the pharmaceutical market in India. Such irrational use of antibiotic FDCs can rapidly give rise to resistant strains of organisms, increasing ADRs and drug interactions which is a serious concern for the health care system. The present study is designed to fill the lacuna in the research regarding rational and irrational FDCs available in the Indian market. OBJECTIVES:1) To analyse rational and irrational FDCs of antibacterial drugs 2) To create awareness about the extensive use of irrational FDCs among the prescribers. METHODOLOGY: Data on FDCs available in the Indian market was collected from the Current Index of Medical Specialities (CIMS) Jan-2022[2] and Drug Today Jan-Apr-2022[3] . Their rationality was analysed based on their pharmacokinetic properties, pharmacodynamic activity, drug interactions and those listed in the WHO Essential List Of Medicines 2021[4] and National List of Essential Medicines (NLEM) 2022[5] .The number of companies producing such combinations were listed. A list of prohibited drugs which are still being circulated was also given. RESULTS: A total of 86 combinations were listed, among which 42 combinations were rational and 44 combinations were irrational. The most common irrational FDC available is Ofloxacin+ Ornidazole, produced by 130 companies. A total of 15 FDCs were found banned but being manufactured by several companies. CONCLUSION: Many Irrational FDCs are being supplied in the Indian market by different companies. Awareness about irrational FDCs, generated among prescribers through our study, will help to avoid the unnecessary risk of ADRs, drug resistance and financial burden on the patient. Hence, scrutiny and a strict review of regulatory framework for FDC manufacturing and marketing is needed for the betterment of patient care in the country.